Hydrocarbon generation kinetics and history of source rocks in different salinity environments, Dongpu Depression, Bohai Bay Basin, China - Chengfu Zhang; Jingyan Liu; Tianwu Xu; Jianhong Yang; Lishuang Lv (PLoS ONE, 2026)
The Dongpu Depression is a typical petroliferous depression characterized by remarkable variations in sedimentary salinity. To investigate hydrocarbon generation characteristics of source rocks in different salinity environments, 20 source rock samples were collected and analyzed for organic geochemical. Combining trace elements, Three representative samples were further selected for gold-tube pyrolysis experiments to obtain hydrocarbon generation kinetic parameters. Integrating constraints from kinetic parameters and thermal history, basin modeling was conducted to systematically compare the hydrocarbon generation characteristics of source rocks in different salinity environments. Results show that activation energy for gaseous hydrocarbon generation is widely distributed, while that for liquid hydrocarbon generation is relatively concentrated. Hydrocarbon yields follow the order: saline environment (SE)> brackish environment (BE)> freshwater environment (FE). High-quality source rock intervals with hydrocarbon generation intensity exceeding 2 × 10⁶ t/km² are recognized as key targets for subsequent oil and gas exploration in the region. This study provides valuable implications for hydrocarbon exploration and resource assessment in comparable saline lacustrine basins.